Trajectory to professorship for third space practitioners: a learning developer perspective - Steve Briggs (Journal of Learning Development in Higher Education)
A higher education (HE) professional with a role that spans across the traditional academic and non-academic dichotomy is described as working within the ‘third space’ (Whitchurch, 2013). Whitchurch (2023) conceptualises the third space as, ‘likely to be plural and to be comprised of multiple spaces, which may continually reconfigure’. Therefore, some staff may work permanently or periodically in the third space. I have worked in the third space as a Learning Developer for almost 20 years. During this time, I have been fortunate to progress in my career from an Academic Skills Tutor to Director of Learning and Teaching Excellence. I have co-chaired the Association for Learning Development in Higher Education (ALDinHE) and am humbled to have received a National Teaching Fellowship in 2020. However, up until around 12 months ago, I had never thought that I could realistically pursue a professorship.